P525 The benefits of anti-TNF drug and antidrug antibody (ADAb) level monitoring in a DGH. (25th January 2019) - Matthews, C; London, I; Reilly, I; Maheswaren, T; Lewis Williams, A; Michail, S
Abstract: Background: There are a number of time points highlighted at which to perform anti-TNF drug and ADAb levels in IBD patients on anti-TNF drugs. These include: at the time of loss of response; after induction; and yearly. Effective therapy is associated with improved quality of life, fewer symptoms and disease and surgery-free survival. Drug level and antidrug antibody (ADAb)-level testing allows a more personalised management, improves patient outcomes and can be associated with significant cost savings. 1 We retrospectively evaluated our increasing use of drug and antidrug antibody levels and reviewed how this has reflected a change in our clinical practice. Methods: Permission to perform a retrospective audit was obtained from our trust. The IBD database was interrogated and all patients on infliximab were included. All patients had been converted to the biosimilar Remsima. Use of anti-TNF drug and ADAb levels in 2016 when compared with 2017 in the same cohort of patients. Our trust uses the ELISA assay like most areas of the UK. Results: 74 patients received infliximab in 2016, 8 patients stopped/switched leaving 66 patients still on infliximab in 2017. 66% of the cohort had Crohn's disease in each year. 70% of patients had been on Infliximab for over 12 months in 2016 compared with 80% of patients in 2017. Levels were checked in 14% (9) of patients in 2016 and 91% (60) of patients in 2017 (see Table 1). Based on levels in 2016, 5 patients had their anti-TNF stopped (1) or switched (4). Based on levels in 2017, 41 patients had their treatment regimen changed – stopped (15), switched (15), de-escalated (9) and escalated (2). In 2016, the majority of patients (89%) continued their anti-TNF regimen unchanged. In 2017, 15 (23%) patients have continued their treatment unchanged so far. Conclusions: The use of anti-TNF drug and ADAb levels increased dramatically from 2016 to 2017. Profound benefits have been demonstrated with this change. There was improved decision making with the use of anti-TNF drug and ADAb levels in 2017. Treatment was de-escalated or stopped in 40% of patients in whom anti-TNF drug and ADAb levels were checked, reducing the risk of side effects and with a cost saving of £147300 a year in total from those patients stopping Infliximab. Drug level testing in 2017 would have cost approximately £5400.